2005
DOI: 10.1364/josaa.22.001151
|View full text |Cite
|
Sign up to set email alerts
|

Determination of refractive indices of porcine skin tissues and Intralipid at eight wavelengths between 325 and 1557 nm

Abstract: We constructed an automated reflectometry system for accurate measurement of coherent reflectance curves of turbid samples and analyzed the presence of coherent and diffuse reflection near the specular reflection angle. An existing method has been validated to determine the complex refractive indices of turbid samples on the basis of nonlinear regression of the coherent reflectance curves by Fresnel's equations. The complex refractive indices of fresh porcine skin epidermis and dermis tissues and Intralipid so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 19 publications
4
81
1
1
Order By: Relevance
“…However, the use of NIR spectroscopy to analyze in vivo samples or live animals might be limited to the NIR spectral range between 5200 and 4370 cm −1 due to the large effect of water (5263 cm −1 ). Other authors reported similar results when different animal tissues were analyzed using NIR spectroscopy [6,17,27,28].…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…However, the use of NIR spectroscopy to analyze in vivo samples or live animals might be limited to the NIR spectral range between 5200 and 4370 cm −1 due to the large effect of water (5263 cm −1 ). Other authors reported similar results when different animal tissues were analyzed using NIR spectroscopy [6,17,27,28].…”
Section: Resultssupporting
confidence: 55%
“…This region appears to be unique between the different tissues (e.g., fat, muscle, and skin) analyzed, indicating that differences in the absorbance values can be attributed to different protein and collagen ratios between tissues. In the same region, shifts were also observed around 4329 cm −1 (e.g., lipids, collagen, and proteoglycans) and between 4762- [6,17,[23][24][25][26][27]. Overall, the visual inspection of the wavenumber region between 5263 and 4175 cm −1 indicated that long wavelengths in the NIR region can be useful to identify differences between tissues.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The appearance of skin is significantly influenced by the presence of a thin emulsified film on the skin surface. Sebum containing lipids from sebaceous glands and epidermal keratinocytes is mixed with sweat and other lipids from cosmetics and environment to form this emulsified film of refractive index higher than that of the epidermis [8][9]. This thin layer of skin surface lipids provides barrier protection, regulation of transepidermal water loss and maintenance of the skin biofilm [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…By using polarized laser light as the illuminating beam of the prism/tissue setup at different angles, the amount of reflected light is measured. By knowing the RI of the prism at the laser wavelength, the RI of the tissue can be calculated by identifying the critical angle at the prism/tissue interface [1,4,[7][8][9][10]. This method is very simple and it can be used to measure the RI of biological tissues at different wavelengths, provided that lasers at those wavelengths are available.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%